Association between perinatal interventional activity and 2-year outcome of Swiss extremely preterm born infants: a population-based cohort study. Issue 3 (15th March 2019) - Adams, Mark; Berger, Thomas M; Borradori-Tolsa, Cristina; Bickle-Graz, Myriam; Grunt, Sebastian; Gerull, Roland; Bassler, Dirk; Natalucci, Giancarlo
Abstract : Objectives: To investigate if centre-specific levels of perinatal interventional activity were associated with neonatal and neurodevelopmental outcome at 2 years of age in two separately analysed cohorts of infants: cohort A born at 22–25 and cohort B born at 26–27 gestational weeks, respectively. Design: Geographically defined, retrospective cohort study. Setting: All nine level III perinatal centres (neonatal intensive care units and affiliated obstetrical services) in Switzerland. Patients: All live-born infants in Switzerland in 2006–2013 below 28 gestational weeks, excluding infants with major congenital malformation. Outcome measures: Outcomes at 2 years corrected for prematurity were mortality, survival with any major neonatal morbidity and with severe-to-moderate neurodevelopmental impairment (NDI). Results: Cohort A associated birth in a centre with high perinatal activity with low mortality adjusted OR (aOR 0.22; 95% CI 0.16 to 0.32), while no association was observed with survival with major morbidity (aOR 0.74; 95% CI 0.46 to 1.19) and with NDI (aOR 0.97; 95% CI 0.46 to 2.02). Median age at death (8 vs 4 days) and length of stay (100 vs 73 days) were higher in high than in low activity centres. The results for cohort B mirrored those for cohort A. Conclusions: Centres with high perinatal activity in Switzerland have a significantly lower risk for mortality while having comparable outcomes among survivors. This confirms the results of other studies but in a geographically defined area applying a more restrictive approach to initiation of perinatal intensive care than previous studies. The study adds that infants up to 28 weeks benefited from a higher perinatal activity and why further research is required to better estimate the added burden on children who ultimately do not survive.